LNG as Alternative Fuel for European Transport System - Kalina, Tomas; Grobarcikova, Anezka (Communications - Scientific Letters of the University of Zilina, 2014)
This paper gives basic information about Liquefied Natural Gas as a greener alternative to other fossil fuels. It focuses on basic properties of LNG, which are fundamental to understanding LNG correctly and then possibly use it as a fuel for ships, trucks, etc. Furthermore, it focuses on essential parts of a process chain of LNG transport, which is liquefaction, transport of LNG itself and regasification. Closer look is given to the usage of far less preferred alternative for transport, which is inland navigation.
Keywords: energy consumption; fossil fuels; liquefied natural gas; terminals; transport